2018
DOI: 10.1590/0004-282x20180004
|View full text |Cite
|
Sign up to set email alerts
|

Migraine improvement correlates with posterior cingulate cortical thickness reduction

Abstract: Objective The main goal of this study was to correlate migraine improvement, after prophylactic therapy, with cortical thickness changes. Methods Cortical thickness maps were obtained with magnetic resonance imaging (MRI) from 19 patients with migraine before (first scan) and after (second scan) prophylactic treatment, and these were compared with controls using the FreeSurfer MRI tool. Cortical changes were correlated with the headache index (HI). Results Anincrease incortical thickness was found in the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Prior literature on regional morphological alterations in brain gray matter in chronic neuropathic pain subjects have revealed widespread cortical thickness abnormalities. In comparison to healthy controls, subjects with orofacial chronic neuropathic pain showed thicker postcentral gyrus, thinner insular cortex, and thinner cuneus cortex ( Amaral et al, 2018 , Hubbard et al, 2014 , Maleki et al, 2015 , Moayedi et al, 2011 , Parise et al, 2014 , Wang et al, 2017a , Wang et al, 2017b , Yang et al, 2017 ). Our current study adds to the clinical importance of these observations by showing insular cortical thickness is predictive of individual-level 1 year response to surgical interventions for orofacial chronic neuropathic pain like trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature on regional morphological alterations in brain gray matter in chronic neuropathic pain subjects have revealed widespread cortical thickness abnormalities. In comparison to healthy controls, subjects with orofacial chronic neuropathic pain showed thicker postcentral gyrus, thinner insular cortex, and thinner cuneus cortex ( Amaral et al, 2018 , Hubbard et al, 2014 , Maleki et al, 2015 , Moayedi et al, 2011 , Parise et al, 2014 , Wang et al, 2017a , Wang et al, 2017b , Yang et al, 2017 ). Our current study adds to the clinical importance of these observations by showing insular cortical thickness is predictive of individual-level 1 year response to surgical interventions for orofacial chronic neuropathic pain like trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…A prior migraine study demonstrated that migraine improvement (i.e. reduced time with headache) was associated with cortical thickness changes in the left posterior cingulate [ 50 ]. The putamen participates in sensory-discriminative aspects of pain processing including the determination of pain sensitivity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prior migraine study demonstrated that migraine improvement (i.e. reduced time with headache) was associated with cortical thickness changes in the left posterior cingulate [50].…”
Section: Pain-induced Activationsmentioning
confidence: 99%
“…In their study population, changes in the left posterior cingulate cortex correlated with headache frequency and intensity. 42 Studies with TTH are quite limited. Chen et al reported no significant difference in gray matter density between TTH patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%